Curriculum for Undergraduate Medical Education In Bangladesh- Updated 2012: An Internal Review and Suggestions (Journal of Chittagong Medical College Teachers' Association, 2014)
We like to express our deep gratitude and respects to the concerned experts and authority for presenting us the Curriculum for Undergraduate Medical Education in Bangladesh- Updated 2012. The quality of healthcare is under scrutiny all over the world because of increasing public expectation of their health care services. Therefore a positive change is needed in the role of doctors. The role of teachers and students in teaching —learning with positive changes in medical education, its strategy and process also needs to be reviewed periodically and updated as to the international standard. (Professor Khondhaker Md Shefyet Ullah Former DG, DGHS). It can be mentioned that the curriculum planning process is continuous, dynamic and never ending. Factors contributing to an effective medical education system are the quality of students, quality of teaching staff, and their effective delivery of need based scientific curriculum. If it is to serve the best, the needs and availability of the resources of the individual institutions should be assessed and be utilized rationally and perfectly.JCMCTA 2014 ; 25 (2) : 73-75